1963
DOI: 10.1113/jphysiol.1963.sp007070
|View full text |Cite
|
Sign up to set email alerts
|

The nervous regulation of the sweating apparatus of the human skin, and emotive sweating in thermal sweating areas

Abstract: Observations on the neural regulation of the human sweat apparatus may help to clarify two outstanding problems concerning the functioning of the skin. It has been known since the work of Kuno andhis school (1956) that the emotive type of sweating is confined to specific area-s of the skin, palms, soles, axillae and limited parts of the face. These commence sweating possibly within a second after the application of a stimulus, such as mental arithmetic, discussion of an embarrassing topic, or physical exercise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0
1

Year Published

1966
1966
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 6 publications
2
17
0
1
Order By: Relevance
“…If the theory of Kuno (1956) and Kennard (1963) is correct, the emotional sweat response of areas other than the hands and feet at 26°C might be expected to be much less than that at 290 C. However, highly significant responses were observed from the hands and feet and from the rest of the body at both temperatures. There was no significant difference between the responses of either region at 260 C and their response at 290 C. It therefore seems unlikely that the skin of the rest of the body can respond to emotional stimuli only when close to or above the thermal sweating threshold.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…If the theory of Kuno (1956) and Kennard (1963) is correct, the emotional sweat response of areas other than the hands and feet at 26°C might be expected to be much less than that at 290 C. However, highly significant responses were observed from the hands and feet and from the rest of the body at both temperatures. There was no significant difference between the responses of either region at 260 C and their response at 290 C. It therefore seems unlikely that the skin of the rest of the body can respond to emotional stimuli only when close to or above the thermal sweating threshold.…”
Section: Discussionmentioning
confidence: 94%
“…The local methods of sweat estimation employed by McGregor (1952), Kuno (1956) and Kennard (1963) may have contributed to their failure to detect emotional sweat responses from the limbs and trunk of subjects below the thermal threshold since these areas have comparatively low sweat-gland densities. Differences in environmental conditions and strength of emotional stimuli employed may also help to account for apparent discrepancies between their results and the present observations.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, sweat response to mental stimuli may appear on the general body surface only when close to or above the thermal sweating threshold. Even in a temperate environment, however, neural impulses for thermal sweating still reach the sweat glands and mental effects can be visualized on a focal area where local sweating has been provoked by a suforific agent (KENNARD, 1963;OGAWA, 1970;OGAWA and BULLARD, 1972). Furthermore, a small number of functional sweat glands have been detected on the general body surface in a temperate environment (RANDALL, 1946;NAKAYAMA and ARIMURA, 1955), and it has also been reported that there are no significant regional differences in sweat responses to emotional stimuli within the comfort zone (ALLEN et al, 1973).…”
Section: Discussionmentioning
confidence: 99%
“…As for the mechanism underlying such regional differences , however, explanations are controversial among investigators (KUNO, 1956;KENNARD, 1963;NAKAYAMA , 1969).…”
mentioning
confidence: 99%
“…palms and soles) [53]. However, more compelling data support the notion that emotion-evoked sweating is not limited to particular regions of the body but is a generalised phenomenon, although such sweating (or corresponding electrodermal activity) may only be visible on the palms, soles, axilla and face at normal room temperatures [40,54,55,56]. Given the regional differences in sweat gland density outlined previously, it is possible that measurable sweat responses are more readily obtained from the palms, feet and axilla, where sweat glands are more numerous compared to other body sites.…”
Section: Localisation Of Psychological Sweatingmentioning
confidence: 99%